Розробка методу раціонального проїзду транспортними засобами регульованих ділянок доріг - Мазилюк, Павло Вікторович (Луцький національний технічний університет, 2019)
Робота присвячена розробленню теоретичних і практичних аспектів раціонального проїзду ТЗ регульованих ділянок доріг із застосуванням методів і засобів автоматизації управління рухом ТЗ. Запропонована методика раціонального проїзду регульованих ділянок доріг тестувалася на теренах України. Установлено, що абсолютна більшість водіїв проїжджають регульовані ділянки доріг нераціонально, що призводить до зменшення кінцевої швидкості проїзду світлофорів або зупинки ТЗ, підвищеної витрати палива, часу проїзду регульованих ділянок доріг, збільшення викидів ШР. Запропонований метод, система його реалізації, дослідно-вимірювальний комплекс, моделі та програмне забезпечення дають змогу в реальному часі опрацювати вхідну інформацію, перевіряти можливість проїзду регульованої ділянки дороги, відображати рекомендоване сповільнення, що дозволяє підвищити ймовірність проїзду ТЗ регульованих ділянок доріг без зупинки. Работа посвящена разработке теоретических и практических аспектов рационального проезда транспортными средствами (ТС) регулируемых участков дорог с применением методов и средств автоматизации управления движением ТС. Предложенная методика рационального проезда регулируемых участков дорог тестировалась на территории Украины, а, в основном, в городе Луцк. Установлено, что абсолютное большинство водителей проезжают регулируемые участки дорог нерационально, что приводит к уменьшению конечной скорости проезда светофоров или остановки ТС, повышенному расходу топлива, времени проезда регулируемых участков дорог, увеличению выбросов вредных веществ. Предложенный метод, система его реализации, исследовательско-измерительный комплекс, модели и программное обеспечение позволяют в реальном времени обрабатывать входную информацию, проверять возможность проезда регулируемого участка дороги, отображать рекомендуемое замедление, что позволяет повысить вероятность проезда ТС регулируемых участков дорог без остановки. The thesis is devoted to elaborate the theoretical and practical aspects of rational passage of the regulated road sections by the vehicles using the methods and means of automation of the vehicle movement control. The offered methodology of rational passage of the regulated road sections was tested on the territory of Ukraine, and basicly in Lutsk city. It was established that absolute majority of drivers pass the regulated road sections non-rationally, what leads to the reduction of final speed of passing the traffic lights or vehicle stop, the increase of fuel consumption, time of passage of the regulated road sections, growth of pollutant emissions. There was developed a method of rational passage of the regulated road sections by the vehicles, the probability of its application depends on the initial movement characteristics of a vehicle, traffic lights operation mode, road conditions. As a result, there was elaborated a system of reflection of recommended movement mode and the algorithm of the system operation, also a research and measuring complex and its software, that allows to imitate the operation of traffic lights object, to get and to process information about the operation mode of traffic lights, to determine the initial characteristics of vehicle movement, to solve an equation about the algorithm of vehicle operation and to reflect the appropriate recommendations for drivers. In software Microsoft Excel there was made a model for checking the possibility of passing a regulated road section in given conditions, in software MATLAB-models of reflecting the final passage speed, passage time, deceleration, fuel consumption, that allow to choose the parameters of vehicle movement which are necessary to realize a work of mathematic device with the aim of rational passage of the regulated road sections. The results of made experimantal researches and calculations show that an offered method allows the drivers to overcome the regulated road sections with minimal fuel and time consumption, and maximum final speed. The offered method, a system of its realisation, a research and measuring complex, the models and software allow, in real time, to process the input data, to check the possibility of passing the regulated road section, to reflect a recommended deceleration that allows to increase a probability of passage of the regulated raod sections by the vehicles without stop.
Разработка метода рационального проезда транспортными средствами регулируемых участков дорог
Development of a method of rational passage of the regulated road sections by the vehicles
Keywords: транспортний засіб; світлофорний об’єкт; регульована ділянка дороги; інтенсивність руху; раціональний проїзд; автоматизація управління; метод проїзду; транспортное средство; светофорный объект; регулируемый участок дороги; интенсивность движения; рациональный проезд; автоматизация управления; метод проезда; vehicle; traffic lights object; regulated road section; movement intensity; rational passage; automation of control; 656.13